Pengaruh Imbal Jasa Penjaminan Terhadap Pertumbuhan Laba PT. Jamkrindo Tahun 2021-2023 - Anggie Efanda (Sammajiva: Jurnal Penelitian Bisnis dan Manajemen, 2023)
Guarantee is an important aspect in business activities to reduce risk and increase the trust of business actors. Guarantee also plays a crucial role in supporting the company's profit growth. This study aims to analyze the effect of guarantee fees on PT Jamkrindo's profit growth from 2021 to 2023. This study uses PT Jamkrindo's financial data from annual reports for the period studied. The results of the analysis show that guarantee fees have a significant effect on PT Jamkrindo's profit growth. The increasing demand for guarantee services indicates an increase in company profits in the study period. On the other hand, fluctuations in market conditions and economic factors have a significant impact on PT Jamkrindo's financial performance, but these effects can be overcome with the right risk management strategy.